Further Evidence of Anthropogenic Impact: High Levels of Multiple-Antimicrobial-Resistant Bacteria Found in Neritic-Stage Sea Turtles - Ming-An Tsai; I-Chun Chen; Zeng-Weng Chen; Tsung-Hsien Li (MDPI AG, 2024)
Background/Objectives: Marine turtles are globally threatened and face daily anthropogenic threats, including pollution. Water pollution from emerging contaminants such as antimicrobials is a major and current environmental concern. Methods: This study investigated the phenotypic antimicrobial resistance and heavy metal resistance genes of 47 Vibrio isolates from different stages of sea turtles (oceanic stage vs neritic stage) from the Taiwanese coast. Results: The results show that a high proportion (48.9%; 23/47) of the Vibrio species isolated from sea turtles in our study had a multiple antimicrobial resistance (MAR) pattern. It was found that Vibrio spp. isolates with a MAR pattern and those with a MAR index value greater than 0.2 were both more likely to be observed in neritic-stage sea turtles. Furthermore, isolates from neritic-stage sea turtles exhibited greater resistance to the majority of antimicrobials tested (with the exception of beta-lactams and macrolides) than isolates from the oceanic-stage groups. Isolates from neritic sea turtles were found to be more resistant to nitrofurans and aminoglycosides than isolates from oceanic sea turtles. Furthermore, isolates with a MAR pattern (p = 0.010) and those with a MAR index value greater than 0.2 (p = 0.027) were both found to be significantly positively associated with the mercury reductase (merA) gene. Conclusions: The findings of our study indicate that co-selection of heavy metals and antimicrobial resistance may occur in aquatic bacteria in the coastal foraging habitats of sea turtles in Taiwan.